2017
DOI: 10.5935/0004-2749.20170092
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and reproducibility of automatic segmentation of retinal layers in healthy subjects using Spectralis optical coherence tomography

Abstract: It is possible to obtain cross-sections from the same location using the device's follow-up mode, making it virtually impossible to distinguish between repeated measurements taken with the device by different examiners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Spectralis is one of the commercially available SD-OCT machines that is commonly used in clinical practice. The machine contains a software algorithm that enables a fast acquisitional cross-sectional retinal scan and generates a highly reproducible automated retinal thickness measurement for total and segmented individual retinal layers [14, 16, 17]. In Spectralis, the retinal thickness values were presented as either the ETDRS (covering a central 10-degree area) or posterior pole (covering a central 24-degree area) analysis formats.…”
Section: Discussionmentioning
confidence: 99%
“…Spectralis is one of the commercially available SD-OCT machines that is commonly used in clinical practice. The machine contains a software algorithm that enables a fast acquisitional cross-sectional retinal scan and generates a highly reproducible automated retinal thickness measurement for total and segmented individual retinal layers [14, 16, 17]. In Spectralis, the retinal thickness values were presented as either the ETDRS (covering a central 10-degree area) or posterior pole (covering a central 24-degree area) analysis formats.…”
Section: Discussionmentioning
confidence: 99%
“…However, this inaccuracy can be significantly reduced by postsegmentation inspection and refinement by a trained operator [42,43]. Regarding individual macular layer thickness measurements, Spectralis segmentation software has proven high repeatability and reproducibility for all layers in all nine ETDRS areas [7,44]. Nevertheless, its accuracy may be significantly affected by image quality or marked anatomical distortion [7,45].…”
Section: Table 1 Demographic and Clinical Characteristics Of The Patients By Groupmentioning
confidence: 99%
“…To the best of our knowledge, our study is the first to analyze the HEYEX software for macular sublayer segmentation in NDD. Cetinkaya et al25 found excellent agreement with repeated measurements using the Spectralis HEYEX software on healthy participants for all individual retinal sublayer thickness values. Heussen et al26 compared automated software with manual correction in healthy participants, and found that manual correction of inner and outer retinal boundary errors yields mean differences of less than 6 μm, which is similar to the axial resolution of SD-OCT devices.…”
Section: Discussionmentioning
confidence: 81%